Evaluation of Autothermal Peat Pyrolysis Realization for Fuel Processing Technologies; Waste and Biomass Valorization; Vol. November - Tabakaev R. B. Roman Borisovich; Astafjev A. V. Aleksandr Vladimirovich; Dubinin Yu. V. Yury Vladimirovich; Yazykov N. N.; Yakovlev V. V. Vadim V. (2017, 2017)
Title screen